Enclosure 3: Harry Partch - Blackburn, Philip (Minnesota American composers forum, 1997)
Winner of a 1998 Deems Taylor Special Citation. Written, compiled and produced by Philip Blackburn. Second pressing.A full-length portrait of an unconventional life, Enclosure Three (ISBN: 0-9656569-0-X) is a luxury limited-edition 528-page, lavishly-illustrated, hardcover art-, bio-, scrapbook of Partch. It is the first biography of one of America's most original and influential artists told through over 1,000 facsimile documents in his own words: 330+ photos; essays; sketches; scores; correspondence with Anaïs Nin, W. B. Yeats, Edmund Dulac, John Cage, Lou Harrison, Martha Graham, Alwin Nikolais, Bruce Goff, Kenneth Anger, and Ben Johnston. Partch's life touched many of the central characters in American twentieth century art, literature, theater, architecture, film, dance and music. For Partch fans and neophytes alike, Enclosure Three contains essential source material for all those interested in unusual lives, Depression-era Americana, cultural history and creative educational approaches. Contents: (include the following satires, writings, and commentaries by Partch himself) A Modern Parable 1 and 2 The Umbilical Chord Still VibratesOn G-String FormalityKPFA lecture seriesManual on the Maintenance and Repair of and the Musical and Attitudinal Techniques for Some Putative Musical InstrumentsSome Old and New Thoughts After and Before The BewitchedDrawings from Bitter Music and End LittoralBach and TemperamentThe KitharaBarstowMusicians as ArtistsNo BarriersThe Ancient MagicA Somewhat SpoofToward a Ritual Music ConsciousnessVerbal Scenarios for Cry From Another Darkness (Delusion of the Fury), The Dreamer That Remains, The Bewitched, and other incomplete works